Developing and validating a knowledge assessment test in science for incoming first year students in a science high school - Villa, Feliciana Cera (1979)
This knowledge assessment test has been developed and validated for use as a component of an entrance test in a science high school. It was intended to cover one of the specific areas to be tested - science. The stages of development that this paper had gone through were: analysis of available elementary science curriculum materials and textbooks in preparation for the construction of the Tables of Specifications; test item writing; sampling of tryout; statistical analysis; and, revision/selection of items for the final form of the test.